The phylogenetic signal of diversification rates. (8th March 2020) - Caron, Fernanda S.; Pie, Marcio R.
Abstract: Hypotheses to explain the causes of diversity gradients have increasingly focused on the factors that actually change species numbers, namely speciation, extinction and dispersal. A common assumption of many of these hypotheses is that there should be phylogenetic signal in diversification rates, yet this assumption has rarely been tested explicitly. In this study, we compile a large data set including 328, 219 species of plants, mammals, amphibians and squamates to assess the level of phylogenetic signal in their diversification rates. Significant phylogenetic signal was detected in all data sets, except for squamates, suggesting not only that closely related clades indeed might share similar diversification rates, but also that the level of phylogenetic signal might vary considerably between them. Moreover, there were intriguing differences among taxa in the rate of decay in phylogenetic autocorrelation over time, underscoring the existence of taxon‐specific patterns of phylogenetic autocorrelation. These results have important implications for the development of more realistic models of species diversification. Abstract : We compile a large data set including 328, 219 species of plants, mammals, amphibians and squamates to assess the phylogenetic signal in their diversification rates. Significant phylogenetic signal was detected in all data sets, except for squamates, suggesting that closely related clades indeed might share similar diversification rates. Moreover, there were intriguing differences among taxa in the rate of decay in phylogenetic autocorrelation over time, underscoring the existence of taxon‐specific patterns of phylogenetic autocorrelation.